Table of Content - - (Journal of natural sciences, life and applied sciences, 2024)
Table of Content1. Necessary measures to prevent the risk of flooding in urban centers in the Wadi Inawen basin  in Morocco: Applied studyDr. Ali Neddama, Dr. Jaouad El-Bazoui, Dr. Abdelouahed Bouberria2. Morphometric and hydrological characteristics of Abo-Habil Basin, western SudanCo-Prof. Ummhani Idris Ahmed
Keywords: Journal of Natural Sciences, Life and Applied Sciences